RAJASTHANI FOLK MUSIC IMPACT ON SOCIETY: राजस्थानी लोक संगीत का समाज पर प्रभाव - Jain, Nisha (International Journal of Research -GRANTHAALAYAH, 2015)
Rajasthan has always been a subject of curiosity for tourists, musicians, craftspeople etc. due to the originality of its civilization and culture in the states of India. The culture of Rajasthan is unique at all times for food, clothing, dance, music and folk songs. The treasury of regional living, food and folk songs is hidden in the cultural culture flourishing in Rajasthan. The rituals here are the center of attraction for women living in the way of living, dress, bright colors, Teej festivals, fairs, festivals, and the men and sarongs that are tied on the head. Rajasthani folk music is sung and played on all special occasions. The dance dramas in Rajasthani songs in the same colorful costumes captivate the minds of the audience. भारत के प्रदेषों में राजस्थान अपनी सभ्यता एवं संस्कृति की मौलिकता के कारण सर्वदा से पर्यटक, संगीतकार, षिल्पकार आदि के लिए कौतूहल का विषय रहा है। राजस्थान की संस्कृति खान-पान, वेषभूषा, नृत्य, संगीत एवं लोक गीतों के लिए प्रत्येक समय में विषिष्ट बनी हुई है। राजस्थान में पल्लवित लोक संस्कृति में क्षेत्रीय रहन-सहन, खान-पान व लोकगीतों का खजाना छिपा हुआ है। यहाँ के रीति-रिवाज रहन-सहन, वेषभूषा, चटकीले रंग, तीज त्यौहार, मेले, पर्व में पहनावा तथा सिर पर साफे बंधे हुए पुरूष एवं घेरदार लहँगे में महिला षहरवासियों के आकर्षण का केन्द्र होती है। राजस्थानी लोक संगीत सभी विषिष्ट अवसरों पर गाए एवं बजाये जाते हैं। राजस्थानी गीतों पर वहीं की रंगीन वेषभूषा में नृत्य नाटिकाएँ दर्षकों का मन मोह लेती हैं।